2019
DOI: 10.1249/mss.0000000000001895
|View full text |Cite
|
Sign up to set email alerts
|

Functional Resistance Training and Affective Response in Female College-Age Students

Abstract: Introduction Although resistance training (RT) can lead to acute improvements in psychological, physiological and psychosocial outcomes, prevalence rates remain low in college-age females likely due to perceived barriers. This study compared the effects of an acute bout of both a functional RT (FRT) and traditional RT (TRT) session on affect, state anxiety enjoyment and physiological measures. Methods Females (n = 34, mean age = 27 ± 4.5 yr) not current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
43

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 30 publications
1
21
0
43
Order By: Relevance
“…The results of our study found the prescribed aerobic exercise and resistance training have positive effects to relieve depressive symptoms of college students. These findings on the effects of exercise interventions in relieving depressive symptoms are consistent with the conclusion of various previous RCT researches ( 31 , 52 , 53 ) and systematic reviews ( 20 , 21 , 32 ). Besides, such positive effect was well-maintained at 4-week post-intervention in our study, which is consistent with previous studies ( 54 , 55 ), so it is possible that prescribed exercise continuously contributed to the participants’ abilities to deal with depressive stress.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study found the prescribed aerobic exercise and resistance training have positive effects to relieve depressive symptoms of college students. These findings on the effects of exercise interventions in relieving depressive symptoms are consistent with the conclusion of various previous RCT researches ( 31 , 52 , 53 ) and systematic reviews ( 20 , 21 , 32 ). Besides, such positive effect was well-maintained at 4-week post-intervention in our study, which is consistent with previous studies ( 54 , 55 ), so it is possible that prescribed exercise continuously contributed to the participants’ abilities to deal with depressive stress.…”
Section: Discussionsupporting
confidence: 91%
“…Although previous research is limited on these topics, there are 3 experiments that have compared the affective responses from machines and free-weights using FS. One experiment found affect to be more positive for free-weight exercises (5) and 2 experiments have found no differences in affect (7,11). These conflicting results suggest interindividual variability among the relationship between exercise modality and affect.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to aggravating factors, there is evidence that university stress may be reduced when engaging in sport activities [22]. Von Rosen et al [23] promoted sport activities as an effective tool in young adults for developing their potential to cope with stress and negative emotions, so it has been considered to be a useful solution to combat stress [24]. It can be especially beneficial in adapting to new environments (such as youth transitioning from secondary to higher education), when young people experience higher levels of stress and anxiety than usual [25].…”
Section: Introductionmentioning
confidence: 99%